Hubungan Intensitas Bermain Game Online dengan Kualitas Tidur dan Perilaku Agresif pada Remaja - Yudi Yulyanto; Solehudin Solehudin; Sancka Stella (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
The development of digital technology has increased the popularity of online games among adolescents. Excessive intensity of online gaming may have negative effects on health, particularly sleep quality and aggressive behavior. This study aimed to determine the relationship between the intensity of online gaming and sleep quality as well as aggressive behavior among tenth-grade students at SMAN 38 South Jakarta in 2025. This research is quantitative associative method with a correlational analytic design using a cross-sectional approach. The population in the study was 145 students, with a sample of 117 respondents selected using random sampling. Data analysis was conducted using the Chi-Square test. The results showed a significant relationship between the intensity of online gaming and sleep quality with a p-value of 0.001 (p < 0.05), as well as a significant relationship between the intensity of online gaming and aggressive behavior with a p-value of 0.001 (p < 0.05). Therefore, the null hypothesis (H0) was rejected and (Ha) was accepted. In conclusion, higher intensity of online gaming is associated with poorer sleep quality and increased aggressive behavior among adolescents. It is expected that adolescents can manage and limit their online gaming time wisely to reduce its negative impact on health and behavior.